Pediatric Electromyography : Concepts and Clinical Applications - McMillan, Hugh J.; Kang, Peter B. (Springer International Publishing : Imprint: Springer, 2017)
This book describes how to perform nerve conduction studies and electromyography in children, and explains the relevant physiology and anatomy crucial to making a diagnosis. Relevant case presentations are included to aid learning, and the authors also focus on the practical applications of the test results, including discussions of major neuromuscular diseases amenable to diagnosis via electromyography. Pediatric Electromyography: Concepts and Clinical Applications is aimed at residents, technologists and staff pediatric neurologists, as a practical guide and exam study guide.
Keywords: Medicine.; Neurology.; Pediatrics.; elektronické knihy; electronic books